VISUAL LESSONS ENHANCING STUDENT ENGAGEMENT USING ARTIFICIAL INTELLIGENCE - Qudratov Hasanali Otabek o‘g‘li (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the design and implementation of visual lessons aimed at enhancing student engagement through Artificial Intelligence (AI) technologies. AI tools enable educators to create adaptive, interactive, and visually appealing educational materials that promote active learning, participation, and knowledge retention. The study emphasizes the pedagogical benefits of AI-driven visual lessons, including personalized learning pathways, real-time feedback, and improved motivation among students. The methodology provides practical guidelines for integrating AI in lesson design to optimize instructional effectiveness and learner engagement.